2010
DOI: 10.1159/000308174
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a New Method for Automated Determination of Bone Age in Japanese Children

Abstract: BoneXpert, an automated method for analysis of hand radiographs of children, has recently been developed and validated in European children. It determines Tanner-Whitehouse (TW) and Greulich Pyle (GP) bone ages (BA). The purpose of this work is to validate BoneXpert BA in Japanese children and determine the following two properties of the method: (1) The accuracy of the BA, i.e. the standard deviation from an experienced Japanese TW BA rater. (2) The precision of the BA, i.e. BoneXpert’s ability to yield the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 14 publications
1
25
1
Order By: Relevance
“…The precision of BoneXpert, defined as the standard deviation (SD) on a single reading, is 0 on the same X-ray and has been conservatively estimated at 0.17 and 0.18 years, respectively, for image series [19], and for assessing the difference between the left and right hand BA of a subject [20]. Comparable human rerating studies yielded a precision SD in the range 0.25–0.82 years [12,16], depending on the experience of the rater.…”
Section: Technical and Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The precision of BoneXpert, defined as the standard deviation (SD) on a single reading, is 0 on the same X-ray and has been conservatively estimated at 0.17 and 0.18 years, respectively, for image series [19], and for assessing the difference between the left and right hand BA of a subject [20]. Comparable human rerating studies yielded a precision SD in the range 0.25–0.82 years [12,16], depending on the experience of the rater.…”
Section: Technical and Methodological Considerationsmentioning
confidence: 99%
“…The impact of a poor precision can be illustrated by two examples: for a 13-year-old boy with a height of 160 cm, BA values of 13 and 13.82 years yield a difference of 6.1 cm in adult height prediction, and for an 11-year-old girl with a height of 150 cm, BA values of 11 and 11.82 years yield a difference of 4.0 cm. In the search for an objective validation that goes beyond comparing the automated BA to that of trained manual raters, it was found that its correlation with growth potential, and therefore its ability to predict adult height, was at least as good as the GP rating and better than the TW rating of the raters of the First Zurich Longitudinal Study [21]. …”
Section: Technical and Methodological Considerationsmentioning
confidence: 99%
“…As the morphological development of the skeleton is very similar across the races, the translation of morphology into a formal maturity index or a formal BA is considered to be universal, i.e. independent of ethnicity and whether the children show normal or abnormal maturation [8], even though BoneXpert is based on the data from European children. …”
Section: Discussionmentioning
confidence: 99%
“…This means that BoneXpert showed a consistent bias to underestimate the BA of Chinese children who were >10 years of age. Other researchers in mainland China, Taiwan and Japan have also pointed out that normal Asian children are inclined to mature faster than their counterparts in Europe [8,11,20]. Even in America, Asian children who are older than 12 years of age were about 1 year advanced relative to the GP standard [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation